Experimental infection of bovines with oocysts of Toxoplasma gondii - Costa, A. J.; Araujo, F. G.; Costa, J. O.; Lima, J. D.; Nascimento, E. (My University, 1977)
Calves aged 3 mth were readily infected with oocysts and cysts of Toxoplasma gondii administered by the oral route. Fever, respiratory distress, nasal discharge, and hyperemia of the conjunctivas were the most significant clinical signs noted in the infected animals. Parasitemia was demonstrated in all infected calves. It occurred on different days and up to 62 days after the infection. Toxoplasma was demonstrated in tissues of all infected calves, and the organ most frequently parasitized was the lymph node. Parasitism of the retina was demonstrated in 2 calves. All infected animals had antibody against T. gondii in their serum. The Sabin-Feldman dye test and the indirect immunofluorescent test were both useful in detecting antitoxoplasma antibody.
Keywords: antibody production; cattle; major clinical study; microorganism; oocyst; theoretical study; toxoplasma gondii; Animals; Antibodies; Blood; Cat Diseases; Cats; Cattle; Cattle Diseases; Fever; Lymph Nodes; Mice; Toxoplasma; Toxoplasmosis, Animal